Mutant P53 expression in chronic myeloid leukemia - Areej E. Kadhom; Haider H. Al-Shammari (مجلة كلية الطب, 2013)
Background: Chronic Myeloid Leukemia (CML) occurs due to malignant transformation of a pluripotent stem cell.  Progression is insidious from chronic to aggressive accelerated or blastic phases. Studies revealed a significant role of the tumor suppressor gene P53 in disease progression.